The Underlying reasons of the preferred areas of electives for bachelor of science in nursing students among selected schools in Metro Manila : a study - Sendino, Florencio S. Jr. (Manila : National University, 2008)
The setting of the study is the College of Nursing. The research focused more on the main reasons why students choose the following area of elective.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.